Culture shapes emotion perception from faces and voices: changes over development. Issue 6 (18th August 2021) - Kawahara, Misako; Sauter, Disa A.; Tanaka, Akihiro
ABSTRACT: The perception of multisensory emotion cues is affected by culture. For example, East Asians rely more on vocal, as compared to facial, affective cues compared to Westerners. However, it is unknown whether these cultural differences exist in childhood, and if not, which processing style is exhibited in children. The present study tested East Asian and Western children, as well as adults from both cultural backgrounds, to probe cross-cultural similarities and differences at different ages, and to establish the weighting of each modality at different ages. Participants were simultaneously shown a face and a voice expressing either congruent or incongruent emotions, and were asked to judge whether the person was happy or angry. Replicating previous research, East Asian adults relied more on vocal cues than did Western adults. Young children from both cultural groups, however, behaved like Western adults, relying primarily on visual information. The proportion of responses based on vocal cues increased with age in East Asian, but not Western, participants. These results suggest that culture is an important factor in developmental changes in the perception of facial and vocal affective information.